2023
DOI: 10.1002/smll.202206715
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Scale Room‐Temperature Synthesis of Solid‐State Fluorescent Carbon Nanodots for Bright Electroluminescent Light Emitting Diodes

Abstract: The reaction conditions of high temperature and high pressure will introduce structural defects, high energy consumption, and security risks, severely hindering the industrial application of organic carbon nanodots (CDs). Moreover, the aggregation caused quenching effect also fundamentally limits the CDs based electroluminescent light emitting diodes (LEDs). Herein, for the first time, a rapid one‐step room temperature synthetic strategy is introduced to prepare highly emissive solid‐state‐fluorescent CDs (RT‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Self‐assembled structures can also greatly limit vibrational rotation in CDs, which is the key to achieving solid‐state luminescence. [ 157–159 ]…”
Section: Construction Strategy For Solid‐state Fluorescence Of Carbon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐assembled structures can also greatly limit vibrational rotation in CDs, which is the key to achieving solid‐state luminescence. [ 157–159 ]…”
Section: Construction Strategy For Solid‐state Fluorescence Of Carbon...mentioning
confidence: 99%
“…[ 118 ] Alternatively, intermolecular forces can arrange small molecular precursors in J‐aggregation during carbonization, and this misaligned parallel arrangement can reduce or avoid direct π  π contact, thus allowing SSF (Figure 8b). 159 ]…”
Section: Mechanism Of Solid‐state Fluorescence Of Carbon Dotsmentioning
confidence: 99%
“…[ 7‐11 ] CDs have been widely used in sensing, in vitro / in vivo imaging, cancer therapy, catalysts and optoelectronic devices. [ 12‐19 ] Despite the well documented fluorescent properties, CDs with RTP have also been reported by several groups. [ 20 ] Lin and co‐workers reported the production of effective RTP by aggregation‐induced of CDs in trimellitic acid.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Carbon dots have attracted a significant amount of attention owing to their superior optical properties, , low toxicity, favorable biocompatibility, and stability, showing great potential in many applications, such as photocatalysts, optoelectronic devices, biological imaging, chemical analysis, etc. Up to now, various methodologies for the synthesis of CDs like electrophoresis, the hydrothermal method, the microwave method, and the solvothermal method have been reported. Benefiting from these methods above, many types of full-color CDs have been prepared, and the optical properties were deeply studied. , In 2018, Xiong et al reported a new solvent-controlled synthetic route, which achieved an effective regulation of the dehydration and carbonization processes by only changing the reaction solvent, resulting in highly luminescent CDs with PL emissions from 443 to 745 nm .…”
Section: Introductionmentioning
confidence: 99%